2003
DOI: 10.1074/jbc.m308553200
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-dependent Coproporphyrinogen III Oxidase (HemF) from Escherichia coli Is Stimulated by Manganese

Abstract: During heme biosynthesis in Escherichia coli two structurally unrelated enzymes, one oxygen-dependent (HemF) and one oxygen-independent (HemN), are able to catalyze the oxidative decarboxylation of coproporphyrinogen III to form protoporphyrinogen IX. Oxygendependent coproporphyrinogen III oxidase was produced by overexpression of the E. coli hemF in E. coli and purified to apparent homogeneity. The dimeric enzyme showed a K m value of 2.6 M for coproporphyrinogen III with a k cat value of 0.17 min ؊1 at its o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
57
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 26 publications
3
57
0
Order By: Relevance
“…Under reaction conditions that successfully demonstrated CPO activity for the enzyme from E. coli (30), no conversion of the starting material was observed for the SaHemQ. These results are consistent with prior work using heme-containing HemQ proteins from M. tuberculosis and B. subtilis (15).…”
Section: Apo-hemq Does Not Catalyze Coproporphyrinogen Oxidation-supporting
confidence: 82%
See 1 more Smart Citation
“…Under reaction conditions that successfully demonstrated CPO activity for the enzyme from E. coli (30), no conversion of the starting material was observed for the SaHemQ. These results are consistent with prior work using heme-containing HemQ proteins from M. tuberculosis and B. subtilis (15).…”
Section: Apo-hemq Does Not Catalyze Coproporphyrinogen Oxidation-supporting
confidence: 82%
“…The resulting reduced porphyrinogen was resuspended at an approximate concentration of 6.7 mM in argon-purged 250 mM Tris-HCl buffer supplemented with 1 mM EDTA and 100 mM sodium thioglycolate for stabilization of the porphyrin in its reduced state (30). Three 500-l reactions were prepared aerobically in 15-ml culture tubes with varying concentrations of coproporphyrinogen (100, 500, and 1000 M) and 0.4 mg/ml apo-HemQ per reaction mixture.…”
Section: Methodsmentioning
confidence: 99%
“…HemF and HemN, which catalyze the oxidative decarboxylation of coproporphyrinogen to protoporphyrinogen, function in a stepwise fashion with the production of monovinyl, monopropionyl porphyrinogen, followed by decarboxylation of a second ring propionate to make protoporphyrinogen and the overall production of two molecules of CO 2 . HemF uses molecular oxygen as an electron acceptor, and the enzyme from E. coli has been shown to be stimulated by Mn (42). A model for catalysis by the HemF-type coproporphyrinogen oxidase proposed by Lash (43) has current acceptance.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the oxygen-dependent CPO (odCPO) enzymes (Hem13p) encoded by eukaryotes (and some prokaryotes) employ a very different mechanism. There are reports of requirements for copper (8) and manganese (9), although other studies found no metal ion or other cofactor dependence (except O 2 ) for odCPO activity (10 -12). Regardless of mechanistic details, the first decarboxylation has been shown to be the rate-limiting step for the overall reaction, and transient formation of the 3-carboxyl intermediate harderoporphyrinogen has been demonstrated (13,14).…”
mentioning
confidence: 99%